Examining the Association between Optimal Hedging Strategy and Cost of Capital: Evidence from Egypt - Menna Gamal; Magdy Abdel-Kader; Kholoud Abdelkarim (Journal of Accounting, Business and Management (JABM), 2026)
This paper aims to examine whether the adoption of the optimal additional hedging strategy, which was developed through an optimization model by Ebach et al. (2016), contributes to reducing the cost of capital (COC) arising from the high degree of the risk of earnings volatility which induced by way of measuring financial derivatives at fair value method. The analysis is performed on all 13 Egyptian banks listed in Egyptian exchange (EGX 100) from 2015-to 2020, resulting in 78 observations. Pearson correlation and multiple regression analysis are used to test the research hypothesis. Findings of the study showed a strong negative significant association between the optimal hedging strategy (OHS) and COC, which implies that the application of the optimal additional hedging strategy developed by Ebach et al. (2016) leads to reducing the costs of earnings volatility which represents the COC.